Characterization of the attachment of Treponema pallidum (Nichols strain) to cultured mammalian cells and the potential relationship of attachment to pathogenicity. - Fitzgerald, T J (Infect Immun, 1977)
The interaction of Treponema pallidum (Nichols strain) with 19 different cultured mammalian cell types was examined. These types included cells derived from testis, kidney, spleen, lung, epidermis, cervix, urethra, and nerve tissue of human, rabbit, or rat origins. They represented normal and malignant cells, epithelial and fibroblastic morphology, cell lines, and cell strains, Large numbers of organisms attached to the cultured cells; this attachment prolonged the time of retention of active treponemal motility. Attachment was examined in terms of the number of treponemes inoculated, cultured cells present, and actively growing versus stationary cultured cells; the motility of the treponemes; the viability of the cultured cells; and the different cell passages. In sharp contrast to the attachment of T. pallidum, 11 nonpathogenic treponemes failed to attach to cultured cells. Immune syphilitic rabbit serum prevented the attachment of T. pallidum to cultured cells, as indicated by phase contrast microscopy and rabbit inoculations. This blockage of attachment by immune serum occurred without interfering with active motility of the organisms. Results are discussed in terms of the potential relationship of attachment to the pathogenicity of T pallidum. IMAGES: